Information of Medical Malpractice and Risks in The Informed Consent Process Before Surgery in Indonesia - Sutarno Sutarno; Maryati Maryati (Yustisia, 2021)
This study examines Indonesian statuary regulation that requires doctors or hospitals to explain the medical malpractices or risks to surgery patients during the informed consent process. The study was triggered by the frequent medical disputes caused by the patient's misinformation regarding possible medical malpractices or risks related to surgery. In this case, patients need transparent and relevant information during the informed consent process. Therefore, this study examines the statuary regulation that requires doctors or hospitals to explain the medical malpractices or risks to surgery patients during the informed consent process. It used secondary data collected from literature studies of relevant materials and analyzed using normative and qualitative methods. The results indicated that no statutory regulation requires doctors to explain the medical malpractices and risks associated with surgery during the informed consent. This means that the required transparency principle is often not implemented. Therefore, these laws are urgently needed because the public is misinformed about medical malpractices and risks